Impacto en la información contable en el estado de situación financiera y estado de resultados integrales en las empresas de servicio presentándola bajo NIIF (2017)
In this article, it is intended to describe the main impact generated in the services companies in relation to main financial states (statement of income and financial situation income ) given by implementation of international standard of financial data in Medellin, Colombia, Starting from the fact of a documentary analysis that demonstrates the alteration in the presentation of the financial situation of the service entities, from the results were contrasted with surveys done to students of public accounting, public accounting teachers and accountant who performs in their job. Therefore will be studied deeply this topic and will be shown with facts the impacts generated by convergence of IFRS, in this order of ideas it will be determined what item will affect in a long term buy in any chase will be generated a great reliability in a reported information, this will be useful as a basement in a decision making